Dermal, inhalation, and internal exposure to 1, 6-HDI and its oligomers in car body repair shop workers and industrial spray painters. Issue 9 (25th May 2006) - Pronk, A; Yu, F; Vlaanderen, J; Tielemans, E; Preller, L; Bobeldijk, I; Deddens, J A; Latza, U; Baur, X; Heederik, D
Abstract : Objectives: To study inhalation and dermal exposure to hexamethylene diisocyanate (HDI) and its oligomers as well as personal protection equipment (PPE) use during task performance in conjunction with urinary hexamethylene diamine (HDA) in car body repair shop workers and industrial spray painters. Methods: Personal task based inhalation samples (n = 95) were collected from six car body repair shops and five industrial painting companies using impingers with di-n-butylamine (DBA) in toluene. In parallel, dermal exposure was assessed using nitril rubber gloves. Gloves were submerged into DBA in toluene after sampling. Analysis for HDI and its oligomers was performed by LC-MS/MS. Urine samples were collected from 55 workers (n = 291) and analysed for HDA by GC-MS. Results: Inhalation exposure was strongly associated with tasks during which aerosolisation occurs. Dermal exposure occurred during tasks that involve direct handling of paint. In car body repair shops associations were found between detectable dermal exposure and glove use (odds ratio (OR) 0.22, 95% confidence interval (CI) 0.09 to 0.57) and inhalation exposure level (OR 1.34, 95% CI 0.97 to 1.84 for a 10-fold increase). HDA in urine could be demonstrated in 36% and 10% of car body repair shop workers and industrial painting company workers respectively. In car body repair shops, the frequency of detectable HDA was significantly elevated at the end of the working day (OR 2.13, 95% CI 1.07 to 4.22 for 3–6 pm v 0–8 am). In both branches HDA was detected in urine of ∼25% of the spray painters. In addition HDA was detected in urine of a large proportion of non-spray painters in car body repair shops. Conclusion: Although (spray) painting with lacquers containing isocyanate hardeners results in the highest external exposures to HDI and oligomers, workers that do not perform paint related tasks may also receive a considerable internal dose.